Characterization of a Nicotiana tabacum phytochelatin synthase 1 and its response to cadmium stress - Wu, Chanjuan; Zhang, Jie; Chen, Mei; Liu, Jikai; Tang, Yunlai (Frontiers in Plant Science, 2024)
Phytochelatin synthase (PCS) is a critical enzyme involved in heavy metal detoxification in organisms.In this study, we reported molecular and functional characterization of the PCS1 gene from Nicotiana tabacum. The amino acid sequence of NtPCS1 shared a high similarity in its N-terminal region with PCS from other species. The enzymatic activity of NtPCS1 was found to be enhanced in the order Ag 2+ > Cd 2+ > Cu 2+ > Pb 2+ > Hg 2+ > Fe 2+ > Zn 2+ . In addition, RT-PCR data indicated that NtPCS1 gene is constitutively expressed, with the highest expression observed in flowers, and that its transcript levels are up-regulated by CdCl2. When tobacco overexpressing NtPCS1 (PCS1 lines) were grown under CdCl2 stress, they produced more phytochelatins (PCs) than WT plants, but this did not result in increased Cd accumulation. However, in a root growth assay, the PCS1 lines exhibited hypersensitivity to Cd. The overexpression of NtPCS1 itself does not appear to be the primary cause of this heightened sensitivity to Cd, as the Arabidopsis thaliana Atpcs1 mutant overexpressing NtPCS1 actually exhibited enhanced tolerance to Cd. Furthermore, the addition of exogenous glutathione (GSH) progressively reduced the Cd hypersensitivity of the PCS1 lines, with the hypersensitivity even being completely eliminated. Surprisingly, the application of exogenous GSH led to a remarkably enhanced Cd accumulation in the PCS1 lines.